PENGEMBANGAN SEA FARMING BUDIDAYA KERAMBA JARING APUNG (KJA) KERAPU (EPHINEPHELUS SP.) DI INDONESIA - Gunarto, Anton (LPPM Universitas Terbuka, 2003)
Seafarming is an activity of culturing marine organisms, which encompasses broodstock selection, spawning, hatchery, juvenile culture, and mature stages. At the last stage, the fish, once resist to diseases and weather fluctuation, is released to water bodies for restocking purposes. Through restocking, fisherman's cathces are expected to increase in a sustainable manner. One of the technology that can be used for seafarming is grouper cage culture. This technology is quite productive and intensive, with net cages construction are anchored to float at coastal waters. Cage culture of grouper has a good prospective in Indonesia as the fish is highly valued in international market. Furthermore, Indonesia has very high potential coastal waters for grouper cage culture expansion